(3cJGH GdCdajf GdaGQb Hjf GdUOb hGdejfs - (3GdMdj, CHh efUhQ, GHf GdeWgQ, LeGd GdOjf, GdMSf Hf jhSa Hf Ydj GHf GdeWgQ, J (B726(3g`s ((3cdH Ydj Hf fGO Ydjs)
(3ChdgG (B:s
(3HJQ LRA ef GdaGJMI,hChdg(B: ... (3CeG HYO aEf CVYa YHGO Gddg JYGdi MSf(B...(3GdMdj jbhd CLHJ SDGd hdOj(B...s
(3BNQgG (B:s
(3bhdg JYGdi(B{(3ddPjf CMSfh GdMSfi(B..} (3GdBjI cd EeGe OGY(B...(3gPG BNQ eG hLOfG ef cJGH GdGdajf(B...s
(3JHUQI GdeDda (B:s
(3aj GdCYdGe(B: (3hjbGd(B: (3GdMSjfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdGYdGe(B:(3L(B2(3,U(B227s
(3GdPQjYI(B:(3L(B2(3,U(B292(3,Qbe(B1199s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds